Restless legs syndrome in patients on chronic hemodialysis in a Brazilian city: frequency, biochemical findings and comorbidities - Gilberto S. Goffredo Filho; Cláudia C. Gorini; Andrei S. Purysko; Herta C. Silva; Ibrahim Eduardo F. Elias (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate the frequency of restless legs syndrome (RLS) in patients with chronic renal failure (CRF) in Petrópolis, Brazil, and investigate associations between the syndrome and: demographic characteristics, biochemical variables and comorbidities. METHOD: A cross-sectional study in which we interviewed 176 patients on dialytic therapy based on criteria elaborated by the International Restless Legs Syndrome Study Group, and compared data of patients with and without RLS. RESULTS: The frequency was 14.8 %. There were no significant differences between the two groups in demographic and biochemical variables investigated (iron, creatinine, intact parathyroid hormone, hemoglobin, calcium, phosphate). We found no association between RLS and the most common comorbidities, except for chronic glomerulonephritis (CGN) (OR = 3.84, p < 0.01). CONCLUSION: In the studied population RLS is a common disorder, and is not associated with the investigated biochemical abnormalities. A higher frequency of RLS in subjects with CGN is a finding that needs further investigation.